Alterations in leukocyte counts in Barbari goats experimentally infected with Haemonchus contortus - Sharma, D K; Chauhan, P.P S; Agrawal, R D (The Indian Journal of Animal Sciences, 2005)
Fluctuation in blood leukocyte in 12 male Barbari goats 9-12 months old orally infected with 5 000 Haemonchus contortus larvae (L3) were monitored. The animals were divided in groups A and B, having 8 infected and 4 control animals respectively. Animals of group A were orally administered with 5 000?3 of H. contortus rally while animals in group B were kept as uninfected controls. Both the groups were bled weekly and leukocytic cells counts were determined. Animals infected with H. contortus exhibited a significant decline in levels of neutrophils and lymphocytes counts. However, the levels of eosinophils, basophils ond monocytes counts remained unaffected.